Primary Versus Revision Surgery in the Setting of Adult Spinal Deformity: A Nationwide Study on 10, 912 Patients. Issue 21 (November 2015) - Diebo, Bassel G.; Passias, Peter G.; Marascalchi, Bryan J.; Jalai, Cyrus M.; Worley, Nancy J.; Errico, Thomas J.; Lafage, Virginie
Abstract : Study Design: Retrospective review of a prospectively collected database. Objective: This study compares patient demographics, incidence of comorbidities, procedure-related complications, and mortality following primary versus revision adult spinal deformity surgery Summary of Background Data: Although adult spinal deformity (ASD) surgery has been extensively investigated, no previous study has provided nationwide estimates of patient characteristics and procedure-related complications for primary versus revision spinal deformity surgery comparatively. Methods: Nationwide Inpatient Sample data collected between 2001 and 2010 was analyzed. Discharges with procedural codes for anterior and/or posterior thoracic and/or lumbar spinal fusion and refusion were included for patients aged 25+ and 4+ levels fused with any diagnoses specific for scoliosis. Patient demographics, comorbidity, and procedure-related complications incidence were determined for primary versus revision cohorts. Multivariate analysis reported as (OR [95% CI]). Results: Discharges for 9133 primary and 850 revision cases were identified. Patients differed on the basis of demographic and hospital data. Average comorbidity indices for the cohorts were similar ( P = 0.580), as was in-hospital mortality ( P = 0.163). The incidence of procedure-related complications was higher for the revision cohort (46.96 % vs. 71.97%, P = 0.001). The mean hospital course for the revision cohort was longer (6.37 vs. 7.13 days, P < 0.0001). Revisions had an increased risk of complications involving the nervous system (1.34[1.10–1.6]), hematoma/seroma formation (2.31[1.92–2.78]), accidental vessel or nerve puncture (1.44[1.29–1.61]), wound dehiscence (2.18[1.48–3.21]), postop infection (3.10[2.50–3.85]), and ARDS complications (1.43[1.28–1.60]). The primary cohort had a decreased risk for GI (0.65[0.55–0.76]) and GU complications (0.71[0.51–0.99]). Conclusion: Relative to primary cases, those undergoing revision correction of spinal deformity have a higher risk of many procedure-related complications with a longer hospital course despite similar baseline comorbidity burden and the in-hospital mortality rate. This study provides clinically useful data for surgeons to educate patients at risk for morbidity and mortality and direct future research to improve outcomes.